Effectiveness of an Educational Program on Teachers’ Knowledge in The Primary Schools about Coronavirus Disease - Nibras Mohammed Kadhim, Afifa Radha Aziz, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In the 2020 coronavirus pandemic, many countries have closed schools. and as the pandemic resurges in second and third waves, causing an ongoing pandemic in many countries and territories and consequence of school closures and reopening is the widening of inequalities in children’s health and education outcomes. Educators are key to preventing the spread of COVID-19 in educational settings. This study aims to evaluate the effectiveness of educational program on teachers’ knowledge in The Primary Schools about Coronavirus disease. Methods: The study was designed as a quasi-experimental design approach for study group and control group participants employed in Al Rusafa Second Education Directorate Schools in Baghdad City being. A non-probability "purposive" sample selected from Primary School’s Teachers to obtain represent and accurate data. The sample consisted of seventy teachers, (35) teachers enrolled as a control group and (35) teachers enrolled as a study group. The questionnaire's dependability was proven through empirical study, and it was then submitted to specialists for validation. The total number of items in the questionnaire was50. Self-reports were used to collect data, which was then evaluated using descriptive and inferential statistical data analysis. The selection criteria included Only Teachers who did not enter coronavirus disease training courses. The period of the study was initiated from 13st of October /2021 till 20th of April /2022, tested in three periods pre-test, post-test-I, and post-test-II. Results: The results shows The teachers in study group became knowledgeable and aware toward concept and cause of COVID-19; signs and symptoms; transmission methods; diagnosis and treatment; risks and complications; as well as the prevention. Where highly significant differences between study and control group about teacher's knowledge, and no a significant association with their socio-demographic characteristics. Conclusions: In order to improve teachers' knowledge about coronavirus, an educational training programs are essential. The finding revealed that after receiving training, teachers' knowledge improved. The training program is highly successful, there are still many people who do not implement the protocols in a disciplined manner, potentially due to a lack of information and awareness within the community and especially the school environment. Thus, teachers need to be well informed and encouraged of preventive measures and that all teachers should receive coronavirus training to gain the information and skills necessary, in addition reconsidering certified safety measures and standards in schools to match the global standards in light of the coronavirus variants and ahead of winter 2022, through providing adequate preventive commodities, improve ventilation and to plan to build supporting infrastructure commodities to ensure compliance.